Regional integration and the issue of choosing an appropriate exchange-rate regime in Latin America - Escaith, Hubert (ECLAC SantiagoCL, 2002)
Contends that some subregional cooperative modus operandi could offer both an intermediate and more coherent option for Latin America and Caribbean exchange-rate regimes, and the missing link for a concrete institution-building process on which macroeconomic sustainability could be founded. Presents an alternative to the corner solutions of obtaining credibility and flexibility (at the same time).